Layoffs, Equity Theory, and Work Performance: Further Evidence of the Impact of Survivor Guilt - Brockner, Joel; Greenberg, Jeff; Brockner, Audrey; Bortz, Jenny; Davy, Jeanette A.; Carter, Carolyn (Academy of Management Journal, 1986)
This study explored the effects of layoffs on survivors. We assessed subjects' work performance as a function of whether a co-worker had been laid off and the circumstances of that layoff. Consistent with equity theory, subjects worked harder when they believed that a co-worker's dismissal was based on a random process rather than on the relative merits of their and their co-worker's prior performance. Data drawn from questionnaires lent further support to equity theory as an explanation of these results.